Identification of axon‐enriched MicroRNAs localized to growth cones of cortical neurons. Issue 3 (13th September 2013) - Sasaki, Yukio; Gross, Christina; Xing, Lei; Goshima, Yoshio; Bassell, Gary J.; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT There is increasing evidence that localized mRNAs in axons and growth cones play an important role in axon extension and pathfinding via local translation. A few studies have revealed the presence of microRNAs (miRNAs) in axons, which may control local protein synthesis during axon development. However, so far, there has been no attempt to screen for axon‐enriched miRNAs and to validate their possible localization to growth cones of developing axons from neurons of the central nervous system. In this study, the localization of miRNAs in axons and growth cones in cortical neurons was examined using a "neuron ball" culture method that is suitable to prepare axonal miRNAs with high yield and purity. Axonal miRNAs prepared from the neuron ball cultures of mouse cortical neurons were analyzed by quantitative real‐time RT‐PCR. Among 375 miRNAs that were analyzed, 105 miRNAs were detected in axons, and six miRNAs were significantly enriched in axonal fractions when compared with cell body fractions. Fluorescence in situ hybridization revealed that two axon‐enriched miRNAs, miR‐181a‐1* and miR‐532, localized as distinct granules in distal axons and growth cones. The association of these miRNAs with the RNA‐induced silencing complex further supported their function to regulate mRNA levels or translation in the brain. These results suggest a mechanism to localize specific miRNAs to distal axons and growth cones, where they could be involved in local mRNA regulation. These findings provide new insight into the presence of axonal miRNAs and motivate further analysis of their function in local protein synthesis underlying axon guidance. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 397–406, 2014